OPTIMIZING HUMAN RESOURCES: ADAPTING TO EXTERNAL INFLUENCES AND IMPLEMENTING EFFECTIVE HUMAN CAPITAL MANAGEMENT - Lilis Sulastri; Kadar Nurjaman; Iman Supratman (UIN Sunan Gunung Djati Bandung, 2024)
This study investigates the change on human resource (HR) practices within companies, focusing on the shift from traditional labor maximization strategies to an emphasis on work effectiveness and human resource potential in response to crisis conditions. Through analysis, it highlights how external factors and the need for effective Human Capital Management significantly influence HR practices. Company leaders have recognized the necessity to adapt their HR strategies to ensure organizational resilience against unexpected business disruptions. The research confirms that external conditions, such as economic, technological, and socio-cultural changes, necessitate a more strategic approach to HR management. This approach includes refining Human Capital Management practices to better anticipate and prepare for future challenges, thereby enhancing the company's ability to maintain continuity and efficiency during and beyond the pandemic. This study underscores the importance of adaptive and anticipatory HR practices as essential components of organizational strategy in navigating through crises.